Combined Effect of Solar Radiation and Solar Tide Perturbations on the Spacecraft Rosetta about the Comet Wirtanen (Global Journal of Science Frontier Research, 2013)
The purpose of the present paper is twofold . First, is to give summary on Rosetta spacecraft, the first mission ever to orbit and land on a comet which is Wirtanen comet. The second, which is the most important, is to establish general computational algorithm which could be used for the motion of a spacecraft orbiting about asteroid or comet, taking due account of the combined effect of solar radiation and solar tide. The algorithm was applied for the late stage of Rosetta mission about the Wirtanen comet, staring at 10 June 2011, and the variations of the coordinates and velocities are illustrated graphically in the range f ∈ [0, 2 π].
Keywords: solar tide; solar radiation; motion of spacecraft about comet or asteroid